KONSEP OTONOMI DAERAH DALAM HUKUM TATA NEGARA ISLAM - Weni Gusdi Sari; Zainuddin Zainuddin (Institut Agama Islam Negeri Batusangkar, 2021)
This study examines the concept of regional autonomy in Islamic constitutional law about how is the concept of regional autonomy in Islamic State Constitutional Law and how is the autonomy of regional heads in the perspective of Islamic constitutional law. This research is a qualitative research library (Library Research). The data of this study were obtained through the Islamic law/Fiqh research method with a historical approach. After the data has been collected, it is then processed by studying, researching, studying and understanding the concept of regional autonomy in Islamic Constitutional Law referring to the Al-Quran and Hadith and related articels. This study found the following results: (1) The concept of regional autonomy in Islamic constitutional law is practiced in three types of regional government, namely al-imarah al-khashah, al-imarah al-ammah, al-imarah al-istila. (2) The autonomy of the regional head's power in the perspective of fiqh siyasah dusturiyah or Islamic constitutional law is in accordance with the conditions and authority granted by a Khalifah. The Khalifah as head of state gives authority to al-Amir (Head of Region) in the functions of: collecting taxes in the region, managing regional administration and providing services to the people in the region, maintaining security in the region, attracting kharaj and collecting zakat, upholding and disseminating Islam in the region. area, as well as being a prayer priest.